Alla språk i skolan - Ackermann-Boström, Constanze; Mäkipää, Toni; Skovgaard Andersen, Mette; Barfod Lund, Sonja; Nilsson, Maria; Rocher Hahlin, Céline; Granfeldt, Jonas; Oxley, Simeon; Reath Warren, Anne; Gunneriusson Andrew Clarke, Sara; Dinér, Catrin; Elander Malmqvist, Pernilla; et al. (2025)
In our multilingual societies, communication and collaboration between people are more important than ever. One of the school’s most important missions is therefore to provide students with opportunities to develop their linguistic abilities, enhance intercultural and multilingual competence, and learn to navigate diverse cultural contexts. This anthology is intended to offer inspiration, valuable insights, and practical advice to teachers and other school professionals responsible for language teaching and education, as well as to serve as a resource for student teachers, teacher educators, and researchers working with language in an educational context.